Investigation on the people's expectations from municipalities in the area of sport and recreational services in Iran - Imanzadeh, M.; Çoban, B. (My University, 2013)
Municipalities are as one of the most important people cooperation organizations in communities' bureau system(3). In this direction, the role of municipality management with a range view of various duties is very important including development activities, service, cultural and sports in developing of towns, healthy care and providing of facilities for citizen leisure times. The aim of this study is investigation and describing people's expectations from municipalities in the area of sport and recreational services. In the other words, it can help to clarify both sport significance as an effective relational way between citizen and municipalities and people expectations in relationship with this subject and the role of municipality that can be an effective in the promoting present situation. The method of present study has been as describing and measuring method and it has been has been data collection tool of questionnaire. The investigation statistical society of resident citizen is in the city area limits of Ardebil city as province central of Ardebil in northwest of Iran with 420260 population that 4700 people (%1/1 rate) selected as statistical sample. There have been used from SPSS software for statistical evaluate and clarification of relationship between study variant and various statistical methods, frequency, frequency percent, weighted and arithmetic mean and Chi-square (?2). The results showed that municipalities has a great responsibility in providing sport and recreational facilities in the point of view of people and performing of these duties can has an important influence in promoting municipality situation from the people view and also expansion of relationship between citizen and municipality. Also, according to other section from results, a great part of participations in this study didn't have favorite situation and they evaluated own profit rate from present facilities in this field in order to various difficulty in the low limit. © JPES.
Keywords: Municipality; People; Sport